1997
DOI: 10.1200/jco.1997.15.9.3030
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of initial versus late chest irradiation combined with chemotherapy in limited-stage small-cell lung cancer. Aarhus Lung Cancer Group.

Abstract: Timing of CI did not significantly influence the incidence of in-field recurrences, CNS recurrences, or overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(74 citation statements)
references
References 14 publications
1
67
1
2
Order By: Relevance
“…This is supported by some phase III data and three meta-analyses based on literature. Interpretation of the phase III trials investigating the timing of TRT is difficult because the definitions of early and late TRT, the types of chemotherapy used, and the radiotherapy schedules employed have varied among trials [22][23][24][25][26][27][28][29][30]. Of the trials performed, three revealed longer survival for early versus late TRT [23, 29,30].…”
Section: Timing Of Radiationmentioning
confidence: 99%
“…This is supported by some phase III data and three meta-analyses based on literature. Interpretation of the phase III trials investigating the timing of TRT is difficult because the definitions of early and late TRT, the types of chemotherapy used, and the radiotherapy schedules employed have varied among trials [22][23][24][25][26][27][28][29][30]. Of the trials performed, three revealed longer survival for early versus late TRT [23, 29,30].…”
Section: Timing Of Radiationmentioning
confidence: 99%
“…All of the above-described trials involved patients who received PCI after completion of induction chemotherapy or chemoradiotherapy. There have been two studies giving PCI before chemotherapy [10,11]. However, the optimal application time of brain irradiation in relation to administration of chemotherapy was not systematically evaluated.…”
Section: When To Apply Pci In Sclc?mentioning
confidence: 99%
“…Early concurrent thoracic radiation therapy with combination chemotherapy consisting of VP-16/CDDP is a standard treatment for LD-SCLC patients (Perry et al 1987;Pignon et al, 1992;Murray et al, 1993;Jeremic et al, 1997;Work et al, 1997). Twice-daily thoracic radiation therapy and prophylactic cranial irradiation after a CR have recently been added to the standard treatment (Trussi et al, 1999;Takada et al, 2002).…”
Section: Cpt-11-containing Regimens For Ld-sclcmentioning
confidence: 99%